Parasitoids of Diamondback Moth (Plutella xylostella L.) In Abu Jarash region in (Damascus - Syria) (Damascus University Journal of agriculture sciences, 2021)
The parasitoids associated with the Diamondback moth (Plutella xylostella L.) (Lepidoptera:Plutellidae) were surveyed in Abu Jarash region in (Damascus–Syria) between April 2016 and April 2017. Weekly samples were collected from different stages of the insect. Reseults showed  presence of three species Hymenopteran parasitoids from the superfamily Ichneumonoidea, two of them are from Ichneumonidae, Diadegma semiclausum Hellen,Which is larval parasitoid, Diadromus collaris Gravehorst Which is pupal parasitoid and one of them from Braconidae ,Cotesia plutellae Kurdjumov Which is larval parasitoid species. These parasitoids were identified at Biological Control Studies and Research Center Laboratories, (BCSRC), Faculty of Agriculture, Damascus University, Syria using taxonomic keys.
Keywords: Diamondback moth; parasitoids; Syria